A construção de competências organizacionais - análise a partir dos processos de aprendizagem - estudo de caso da empresa Ângelus Ciência e Tecnologia - Dinato, Maria Rosilene Sabino (2008)
The research analyzes the learning process in the construction of organizational competences of the company of technological base, Ângelus Ciência and Tecnologia S.A. The analysis had as starting point the identification of the organizational competences, with base in the resources of the firm. The path of the company was verified along his/her existence, relating the main events that contributed to the significant processes of change. The learning processes with base in the protected theory for Argyris and Shön - simple cycle, double cycle and triple cycle - they are identified in the stages of development of the organization, with prevalence of the learning of simple and double cycle. The challenge current raisin the being the domain of the deutero learning, or learning of triple cycle, in that necessarily the first two should be consolidated. The research is characterized as qualitative, exploratory and descriptive and he/she grew with base in a study of only case. For the collection of data, it was used documentary research, the half-structuralized interview and toolkit, based in Mills et al (2002). Amongst the main results of the research it is had evidences it of that the capacity to innovate is configured as a motor force that deflagra the dynamic processes of collective learning, stimulating the productive and managemental qualification as a whole. The measure that the learning process stops being accidental and he/she becomes a systematic discipline is enlarged the internal possibilities to innovate and to potentiate the competences.